Technology and quality of Skorup - traditional Montenegrin dairy product - Slavko Mirecki; Danilo Tomić; Snežana Vučinić; Milan Marković; Božidarka Marković (Mljekarstvo)
Skorup is Montenegrin traditional dairy product. Its main characteristics are extremely high content of milk fat and centuries-old technology. Due to the specific technology, high nutritional value and its historical heritage, Skorup deserves to be labelled as product with protected designation of origin (PDO) or protected geographical indication (PGI). The purpose of this study was to collect the most important data about Skorup technology and quality and to launch the process of protection. The chemical quality of raw milk was analysed using IR spectrophotometry, the number of somatic cells and total bacteria count by flow cytometry, and Skorup composition by FTIR spectrophotometry. The presence of Escherichia coli, coagulase positive staphylococci and aerobic mesophilic bacteria in Skorup was detected by standard broth base methods. All Skorup samples contained more than 80 % of fat in dry matter, more than 70 % dry matter, approximately 60 % milk fat and 6 % proteins. The sensory characteristics of all samples were excellent, and according to sensory classification, they belong to the highest classes (I and IA). However, five out of twenty samples did not meet requirements for hygienic quality, which implies the urgent need for improvement of hygiene conditions during its production.